2017
DOI: 10.4103/jrpp.jrpp_16_164
|View full text |Cite
|
Sign up to set email alerts
|

An audit of perioperative antimicrobial prophylaxis: Compliance with the international guidelines

Abstract: Objective:Antimicrobial prophylaxis has been demonstrated to lower the incidence of postoperative infection in nearly all types of surgery. The American Society of Health-System Pharmacists (ASHP) guideline summarizes current data on the appropriate use of antibiotic for surgical prophylaxis. The objective of this study was to assess and audit the use of antibiotics in a tertiary care center according to the recommendation of ASHP guideline.Methods:This cross-sectional study was performed using prospective dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
4
18
0
1
Order By: Relevance
“…Surgical antibiotic prophylaxis (SAP) is a high-volume area of prescribing with significant rates of inappropriate prolonged prescription and compliance issues with timing, choice and dose. [1][2][3][4][5][6][7][8]. Inappropriate SAP represents a short-term risk to patients, via unnecessary use, and mid to longterm risks in terms of contributing to antimicrobial resistance, and is therefore logical to target for optimisation of prescribing within hospitals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Surgical antibiotic prophylaxis (SAP) is a high-volume area of prescribing with significant rates of inappropriate prolonged prescription and compliance issues with timing, choice and dose. [1][2][3][4][5][6][7][8]. Inappropriate SAP represents a short-term risk to patients, via unnecessary use, and mid to longterm risks in terms of contributing to antimicrobial resistance, and is therefore logical to target for optimisation of prescribing within hospitals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Report indicates that between 30 and 90% of this antibiotics prophylaxis use is inappropriate [ 10 , 11 ]. Inappropriate use specifically in the area of the antimicrobial selection, timing and the duration of the antimicrobial prophylaxis were commonly observed [ 12 14 ]. Inappropriate usage could leads to increased hospital costs, emergence of resistant microorganisms, and super-infections and increased adverse drug reaction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of a recent study in referral hospitals in Iran suggested that the most frequent microorganisms developing SSIs ( S. aureus , Escherichia coli and coagulase‐negative staphylococci) match those identified in US hospitals . Thus, using ASHP guidelines in our region is logical; however, the feasibility of this guideline needs to be documented . Finally, the nurse in charge of administering a patient's medications recorded the time of administration on paper notes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Thus, using ASHP guidelines in our region is logical; however, the feasibility of this guideline needs to be documented. 31 Finally, the nurse in charge of administering a patient's medications recorded the time of administration on paper notes. Administration documentation error by nursing staff is a potential confounding factor in this study.…”
Section: Discussionmentioning
confidence: 99%